(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2019)
The aim of the present paper is to discuss the sexual offender’s behavior from the behavior-analytic perspective, as well as the possible contributions of this approach to understand this phenomenon. Understanding child sexual abuse as any other human behavior means understanding its phylogenetic, ontogenetic, and cultural determination, a model known as selection by consequence. In this model, behaviors are not "caused" by unique and necessary events but are selected by their consequences. Identifying which contingencies relate to the behavior – including the common characteristics of offenders and cultural variables related to abuse – may enable the development of safer strategies to prevent abuse and intervention with the sexual offender.